Rating scales in psychiatric disorders - why? - Rajachandrasekar, Bhuvaneswari; Vaiyapuri, Sakthivel (International Journal Of Community Medicine And Public Health, 2023)
Clinical and research instruments are available for assessing patients with psychiatric illness along specific dimensions of symptoms, comorbidities, and other health outcomes. Rating scales in clinical practice and research standardize diagnosis and assessment. Here, we focus on rating scales for common psychiatric disorders like schizophrenia, obsessive-compulsive disorder, depression, anxiety disorder, and stress-related disorders. Structured observation is most commonly used with this tool. Here are a few tools with basic characteristics, such as clarity, relevance, variety, objectives, and uniqueness. Rating scales will be discussed in clinical and research settings and future directions in their use. People using scales for commercial purposes should check for access and availability since some scales are copyrighted. The more standardization can be achieved, the easier it will be to compare individuals or groups of individuals. We will be able to assess care quality and outcomes across settings.